Quasi-projective modules and the finite exchange property - Gary F. Birkenmeier (International Journal of Mathematics and Mathematical Sciences)
We define a module M to be directly refinable if whenever M=A+B, there exists A¯⊆A and B¯⊆B such that M=A¯⊕B¯ . Theorem. Let M be a quasi-projective module. Then M is directly refinable if and only if M has the finite exchange property.